2019
DOI: 10.1111/aji.13092
|View full text |Cite
|
Sign up to set email alerts
|

Lectin pathway proteins of the complement system in normotensive pregnancy and pre‐eclampsia

Abstract: Problem:The lectin pathway of the complement system may be involved in the pathogenesis of pre-eclampsia. We aimed to investigate changes in serum concentrations of a broad range of lectin pathway proteins during normal pregnancy and their association with pre-eclampsia, placental infarctions and intrauterine growth restriction (IUGR). Method of study:We included 51 women with normotensive pregnancies and 54 women with pregnancies complicated by pre-eclampsia. Blood samples were obtained at gestational weeks 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…[69][70][71] Recent evidence also suggests the role of complement dysregulation in the development of preeclampsia and fetal growth restriction through lectin pathway proteins. 72 Evidence from mouse models and human studies supports the role of complement activation in the pathogenesis of obstetrical APS. Mice deficient in the complement components (factor C3, C4, C5, and factor B) and mice treated with inhibitors of complement activation (anti-C5 antibody, C5a receptor antagonist peptide, and antifactor B antibody) are resistant to fetal loss induced by APLAs.…”
Section: Antiphospholipid Syndromementioning
confidence: 95%
“…[69][70][71] Recent evidence also suggests the role of complement dysregulation in the development of preeclampsia and fetal growth restriction through lectin pathway proteins. 72 Evidence from mouse models and human studies supports the role of complement activation in the pathogenesis of obstetrical APS. Mice deficient in the complement components (factor C3, C4, C5, and factor B) and mice treated with inhibitors of complement activation (anti-C5 antibody, C5a receptor antagonist peptide, and antifactor B antibody) are resistant to fetal loss induced by APLAs.…”
Section: Antiphospholipid Syndromementioning
confidence: 95%
“…The concentrations of the LP proteins H-ficolin, M-ficolin, mannan-binding lectin (MBL), MBL-associated serine protease (MASP)-1, MASP-2, MASP-3, collectin liver-1, MBL-associated protein of 44 kilodalton (MAp44) and MAp19 were measured in EDTA plasma with time-resolved immunofluorometric assay (TRIFMA) at the Department of Biomedicine, Aarhus University, Denmark. Laboratory analyses were performed as described previously [33][34][35][36][37][38] with the exception of MASP-1 [39] and H-ficolin [40]. In brief, microtiter wells (FluoroNunc, Thermo Scientific™, Hvidovre, Denmark) were coated with specific antibodies or mannan for MBL and acetylated bovine serum albumin for H-ficolin assays.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Finally, an enhancement solution (Ampliqon, Odense, Denmark) was added and subsequently the plates were read by a fluorometer (Victor X5 1 , PerkinElmer). H-ficolin was analyzed using acetylated bovine serum albumin as the capturing agent as described in [40]. MASP-1 analysis was conducted as previously described [39] except that plates were coated with mouse anti-MASP-1 antibodies (clone 1H1G6, lot no A218033050, Genscript, Piscataway, NJ, USA) at 4 μg/ml final concentration in phosphate-buffered saline as described in [40].…”
Section: Laboratory Analysesmentioning
confidence: 99%
“… Beneventi et al, 2020 investigated maternal and fetal plasma levels of leptin in pregnancies complicated by obesity and preeclampsia. The authors found that pregnant women with obesity had higher serum leptin levels than normal-weight subjects with and without hypertension or normotensive subjects with obesity ( Larsen et al, 2019 ; Beneventi et al, 2020 ; Abraham and Romani, 2022 ).…”
Section: Introductionmentioning
confidence: 98%
“…
Background: Preeclampsia is a serious pregnancy complication that affects 5%-10% of the obstetric population.Objective: To study inflammatory markers associated with preeclampsia.Search Strategy: Searches of articles on the topic published over a 10-year period (2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) were performed in three databases (PubMed, Cochrane, and Embase) using the keywords preeclampsia and inflammatory markers. The PubMed search using 10 years and humans as filters retrieved 124 articles.
…”
mentioning
confidence: 99%